Comfort in a cross-sector care delivery model to address birth inequities: Learnings from San Francisco’s Pregnancy Village - Osamuedeme J. Odiase; April J. Bell; Alison M. El Ayadi; KaSelah Crockett; Malini A. Nijagal; Patience A. Afulani (PLoS ONE, 2026)
Introduction Comfort is a key factor in physical and mental health, influencing overall well-being. Though once seen as peripheral to the patient care experience, it is now recognized as a critical outcome. For Black and other historically minoritized birthing individuals—who face racism, disproportionally higher morbidities, and unequal care—comfort is key to a safe, positive pregnancy experience. Innovative, community-driven models designed to improve comfort are therefore needed. San Francisco’s Pregnancy Village (PV) is a novel, cross-sector care delivery model providing a one-stop shop for clinical, city government, and wraparound services in a dignified and uplifting environment for Black and other minoritized pregnant individuals and their families. This study aims to examine comfort at PV and its key predictors. Methods We surveyed 114 participants (57 pregnant/postpartum individuals and 57 family members) between July 10, 2021 and June 30, 2022. Comfort was measured using a 3-item scale capturing the affective dimension of comfort, with scores standardized to 0–100 scale. Additionally, two individual items assessed situational aspects of comfort: (1) discomfort being seen at PV and (2) feeling out of place at PV. We performed univariate, bivariate, and multivariate analyses. Results The mean comfort score was 96.2/100 ( SD = 11.4). Pregnant and postpartum participants, as well as those with limited social support, felt significantly less comfortable with the idea of being seen by friends at PV compared to family members and those with strong social support, respectively. Participants with some higher education and those reporting occasional everyday discrimination felt significantly less out of place at PV than those with a high school diploma or no discrimination experiences. Conclusions The Pregnancy Village model fostered generally high levels of comfort among Black and other minoritized pregnant individuals and their families in San Francisco, California. However, lower comfort levels among pregnant and postpartum individuals, those with lower educational attainment, and individuals lacking social support underscore the need for greater investment in co-led community-institutional, culturally responsive, and trauma-informed care approaches to foster comfort, particularly for those who face the severest inequities.